Philosophical Perspective of Islamic Economics: A Critical Approach to Capitalism and Materialism in the Context of Modernity - Muhammad Syahrul Hidayat (Research of Islamic Economics, 2023)
This study delves into the philosophical viewpoint of Islamic economics concerning capitalism and materialism within the context of modernity. It examines essential aspects like ownership, wealth distribution, and consumption from an Islamic economic perspective and employs a critical approach to analyze the interactions among capitalism, materialism, and modernity. The research adopts a qualitative analytical method, drawing insights from relevant literature and prior studies in the field. The collected data is scrutinized through the lens of Islamic economic principles and relevant philosophical perspectives. The results highlight how the philosophical standpoint of Islamic economics provides an alternative perspective on addressing capitalism and materialism in contemporary times. Islamic economic thought emphasizes principles of social justice, wealth redistribution, and consumption limitations as integral components. The study underscores the significance of integrating moral and ethical values into economic practices to achieve social and spiritual sustainability. By offering insights into the critique of capitalism and materialism from an Islamic economic standpoint, the research encourages further discussions on more sustainable and equitable economic alternatives.